Programa de intervenção comportamental baseada na entrevista motivacional para a melhora da higiene bucal em adultos – um ensaio clínico randomizado - Ortigara, Gabriela Barbieri (2024)
Patient-centered approaches can lead to better outcomes in the treatment of periodontal diseases, but the ideal role of the dentist in utilizing these methods is not yet fully defined. This study aimed to evaluate the effectiveness of motivational interviewing as part of periodontal treatment to improve adults' adherence to proper oral health behaviors and promote better quality of life. A randomized clinical trial of 72 systemically healthy, non-smoking individuals over 18 years of age, with at least 18 teeth, diagnosed with periodontitis (stage I to IV) and with at least 30% of sites with bleeding on probing (BOP), were randomized into two groups. During phases I and II of periodontal therapy, one group received conventional information (CT) and the other group received a motivational interviewing-based approach (MIG). The Gingival Index (GI), Plaque Index (PI), and BOP were evaluated at baseline, 15 days after phase I, and 30 and 60 days after phase II of therapy. The mean difference and effect size were also assessed. Questionnaires were administered to obtain sociodemographic, behavioral, self-perceived oral health, and quality of life data (OHIP-14). Univariate and multivariate analyses to compare means of PI, GI, BOP, and OHIP within and between groups were conducted using the Statistical Package for the Social Sciences (SPSS, version 25). After 60 days of follow-up, both groups showed significant reductions in gingival inflammation, improvements in clinical indices, higher brushing frequency, interdental device use, and better quality of life. However, no statistically significant differences were found between the groups for the outcomes assessed. The results suggest that psychological interventions based on cognitive constructs and motivational interviewing may contribute to improving oral hygiene in patients with periodontal disease. However, their specific clinical effectiveness, as measured by the reduction in plaque and bleeding indices in the short term, cannot yet be conclusively determined.